HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN STRATEGI COPING PADA PENDERITA STROKE RSUD Dr. MOEWARDI SURAKARTA - Hasan, Nur; Rufaidah, Elina Raharisti (TALENTA, 2013)
Stroke is a disease impaired of blood vessel in the brain suddenly. Stroke will be effect of limitation in moving, communicating and thinking. Physical changes that occur in patients withÂ  stroke will beÂ  increased ofÂ  stress,Â  tension, anxiety andÂ  frustration. The appropriate of coping strategies is required to overcome. The coping strategies by stroke patients will be influenced by social support. Social support can reduce the psychological tension and stabilize the emotions of the people with stroke. The purpose of this study are to know the correlation between social support with coping strategies in patients with stroke, to determine the level of social support received byÂ  stroke patients,Â  and to findÂ  copingÂ  strategiesÂ  that are oftenÂ  raisedÂ  by people with stroke. Subjects used is stroke patients, totaling 30 people. The sampling technique used is purposive non-random sampling. The analysis ofÂ  the productÂ  momentÂ  shows theÂ  correlationÂ  ofÂ  0.563Â  withÂ  pÂ  = 0.000 (p = 0.01), itâs means there is a positive and significant correlation between social supportÂ  withÂ  copingÂ  strategiesÂ  in patients withÂ  stroke.Â  Effective contributionÂ  (SE) of social support for coping strategies by 31.7%, so there is still has 68.3% another factor that affects the appearance of coping strategies in patients with stroke.